Nursing students’ learning experience with healthcare-associated infection prevention and control (HAI-PC) in Asian countries: an exploratory qualitative study - Nget, Manndy (2024)
Background: Healthcare-associated infection prevention and control (HAI-PC) education programs in Asian countries seem limited and require improvement and support. Objective: This study explored students’ learning experiences with HAI-PC education programs in Asian countries (two Vietnamese and two Cambodian universities) to support a pedagogical model in HAI-PC. Method: A qualitative exploratory study design was employed, and inductive content analysis was conducted. Students were selected to participate in the focus group to investigate their experiences with HAI-PC using five structured questions. There were 48 nursing students in total from four universities, 28 from 2 universities in Cambodia, and 20 from two universities in Vietnam. Results: The summary results gained from the four universities were synthesized by grouping them into sub-categories and four primary categories, which were students’ HAI-PC competence, students’ current learning methods in HAI-PC Education, the HAI-PC teaching and learning environment, students’ capacity, and entrepreneurial skills in HAI-PC development. Conclusion: This study revealed evidence to improve nursing education in HAI-PC in Asian countries. The new learning method of the simulation scenario and the model fascinated the students; they were happy and more confident about their future careers in practicing HAI-PC skills in their clinical practicum and hospital practice. The current HAI-PC education faces issues related to education and healthcare systems in Asian countries, highlighting the need for improvement.